Application of Mortgage Law Sharia Gold in Indonesia - Krizna Kizmasky; Genius Ladyan Finasisca (Budapest International Research and Critics University, 2022)
Pawning gold is a form of economic transaction activity that is commonly carried out by the people of Indonesia. Gold as a movable object is not only an object of the conventional pawn law applicable in Indonesia, but is also an object of sharia pawning law in Indonesian Islamic law. There are some basic differences between these two practices. This study examines the differences between these two practices. This study discusses the differences between the two pawn practices based on civil law and Islamic law in Indonesia with normative legal research methods based on applicable regulations.